Assessment of Trash Fish and By-Catch yield of Coastal Fisheries in Selected Landing Sites of Jaffna District - Sinnathurai, K.; Sathees, D.; Wijenayake, W.M.H.K. (International Journal for Research in Applied Science & Engineering Technology (IJRASET), 2020)
Jaffna fishery contributes a total fish production of 7% in Sri Lanka in 2016. The current study aims to collect recent updates on the Trash fish and By-catch yield concerning gears in selected landing sites of Jaffna from Dec 2018 to Mar 2019. Primary data were collected through direct observations and questionnaires and the Secondary data from the records of the Department of Fisheries, Jaffna. Total Catch, Species composition, and Fishing craft usage were collected weekly. A sum of 28 species, representing 22 families were identified. Outboard Fiber Reinforced Plastic Boats were primarily used. The highest total fish production was observed in Math gal with an average of 24.5 tons/month and lowest in Ponnalai with 9 tons/month. Higher target fish yield was observed from a ray net with 86.54% gear efficiency and lower in disc net with 38.72%. By catch was observed high in crab net with 41.625% and lower in ray net of 10.84%. Casting net and ray net yields higher and lower trash fish of 30.18% and 2.62% respectively. The results of the present study suggest a need for development in existing facilities. Keywords: By- catch, Coastal fishery, Fishing crafts, Fish production, Gear efficiency
Keywords: Coastal fishery; Fishing crafts; Fish production